A conceptual framework on pre- and post-displacement stressors: the case of Syrian refugees - Assaf, Sara A.; Nuwayhid, Iman; Habib, Rima R. (Frontiers in Public Health, 2024)
Researchers have documented multiple stressors and mental health problems along the journey of refugees as they are displaced to seek refuge in nearby and remote host countries. This article examines published research on Syrian refugees to propose a framework to conceptualize Syrian refugees’ pre- and post-stressors and their collective impact on their mental health. The proposed framework provides a comprehensive understanding of the interconnected pathways between pre-displacement stressors, post-displacement stressors, and mental health outcomes for Syrian refugees. Pre-displacement stressors are best captured by the concept of trauma centrality and emotional suppression. Post-displacement stressors, categorized under financial, political, and social themes, have a direct impact on the mental health of the refugees, but could also play a partial mediating role on the impact of pre-displacement stressors on mental health. The framework suggests a direct pathway between the experience of war-related traumatic events and mental health and introduces the country of residence as a potential moderator of the severity of mental health. The latter is primarily influenced by local policies and the host communities’ acceptance of refugees. We believe that the proposed framework can guide the work of researchers, policymakers, and practitioners concerned with the mental health and well-being of Syrian refugees. Additionally, although based on the experience of Syrian refugees, it presents a holistic perspective that could be adapted in other refugee settings.